Pengaruh Profitabilitas, Likuiditas, Struktur Aset, Ukuran Perusahaan Dan Tingkat Pertumbuhan Terhadap Struktur Modal - Yunia, Fira; Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to examine the effect of profitability, liquidity, company size, asset structure, and growth rate on capital structure. Profitability is measured by return on assets, liquidity is measured by the current ratio, company size is measured by the natural logarithm of total assets, asset structure is measured by the fixed asset ratio, and growth rate is measured by the growth ratio while capital structure is measured by the debt to equity ratio. This type of research is quantitative research. The research population is food and beverage companies listed on the Indonesia Stock Exchange (IDX). The sample in this study was obtained using the purposive sampling method, namely the selection of samples using predetermined criteria. Based on the purposive sampling method, 25 samples were obtained from 72 food and beverage companies listed on the Indonesia Stock Exchange during 2020 - 2023. The data analysis technique used is multiple linear regression analysis with the help of the SPSS program. Based on the results of data analysis and hypothesis testing, it can be concluded that the profitability variable has a positive effect on capital structure, liquidity has a negative effect on capital structure, asset structure has a positive effect on capital structure, company size does not affect capital structure, and growth rate does not significantly affect capital structure.